Elephant movements and human-elephant conflict in a transfrontier conservation area - Von Gerhardt-Weber, Katharina E. M. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScConEcol)--University of Stellenbosch, 2011.